The Subtle Logics of Knowledge Conflicts in China's Foreign Enterprises - Wang, Constanze; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden (Imprint), 2016)
This book investigates knowledge interactions in China's foreign enterprises. It reveals that cultural differences strongly account for knowledge-related obstacles, namely knowledge leakage and insufficient knowledge sharing. Contrary to conventional wisdom, however, widespread cultural arguments such as Confucianism or collectivism hardly apply to Chinese employees' handling of knowledge. In fact, more subtle cultural logics are relevant in daily work, which are connected to the perceived stability of the enterprise itself. But these usually go unnoticed. Thus, rather than being distracted by a national "Chinese culture", managers can take real action to solve knowledge conflicts in their particular enterprise. Contents Intermediaries in China's Foreign Enterprises Knowledge Workers in China The Property of Knowledge in Chinese Philosophy, History, and Law Knowledge Practices and Sino-German Conflicts Target Groups Scholars, lecturers and students in the fields of China studies, business management, sociology, and law Managers, investors and consultants involved in foreign business activities in China The Author Constanze Wang is Global Corporate Communications and Culture Manager for a German engineering company. She is in charge of the company's integration with the Chinese parent company. .
Intermediaries in China's Foreign Enterprises -- Knowledge Workers in China -- The Property of Knowledge in Chinese Philosophy, History, and Law -- Knowledge Practices and Sino-German Conflicts -- Solutions for Sino-German Knowledge Conflicts. .
Keywords: AREA STUDIES